SENSATION SEEKING SCALE: INDIAN ADAPTATION - Basu, Debasish (Medknow Publications, 1993)
Sensation seeking refers to a biologically based personality dimension defined as the need for varied, novel and complex sensations and experiences, and the willingness to take physical and social risks for the sake of such experiences. Although researched worldwide for nearly three decades now, there is to date no published Indian study utilizing the concept of sensation seeking. This paper describes adaptation of the Sensation Seeking Scale for the Indian population. After due modification of the scale, its reliability, internal consistency and discriminant validity were established Norms were developed for a defined segment of general population. This study may be seen as the beginning of research in India on the subject of sensation seeking.